2014
DOI: 10.1007/s10964-014-0098-7
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Origin Youths’ Trajectories of Perceived Peer Discrimination from Middle Childhood to Adolescence: Variation by Neighborhood Ethnic Concentration

Abstract: Developmentally salient research on perceived peer discrimination among minority youths is limited. Little is known about trajectories of perceived peer discrimination across the developmental period ranging from middle childhood to adolescence. Ethically concentrated neighborhoods are hypothesized to protect minority youths from discrimination, but strong empirical tests are lacking. The first aim of the current study was to estimate trajectories of perceived peer discrimination from middle childhood to adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 50 publications
4
76
0
Order By: Relevance
“…Those who did not participate: could not be located, had moved to Mexico, could not presently participate or were difficult to contact, or refused. Across the study period 54.6% of adolescents moved out of their P1 neighborhoods, a rate comparable to prior work (White et al, 2014). …”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Those who did not participate: could not be located, had moved to Mexico, could not presently participate or were difficult to contact, or refused. Across the study period 54.6% of adolescents moved out of their P1 neighborhoods, a rate comparable to prior work (White et al, 2014). …”
Section: Methodsmentioning
confidence: 63%
“…We hypothesized that high Latino ethnic concentration would be associated with: (a) higher initial levels and stability or increases over time in Mexican orientations and (b) lower initial levels and slower growth or declines in Anglo orientations. Because parents' cultural orientations and family socioeconomic circumstances help to explain how and why Latino families select into neighborhoods that vary on Latino concentration (White, Zeiders, Knight, Roosa, & Tein, 2014), and because these variables can also influence cultural adaptations (Knight et al, 2014; Matsunaga et al, 2010; Umaña-Taylor et al, 2014), we included mothers' and fathers' cultural orientations and family socioeconomic circumstances as covariates to reduce neighborhood selection confounds.…”
Section: Current Studymentioning
confidence: 99%
“…Fifth, our participants were from an area with a high percentage of Chinese Americans. As community characteristics such as ethnic concentration may influence the effects of discrimination (White, Zeiders, Knight, Roosa, & Tein, 2014), future studies should test whether our results can be replicated in other Chinese American samples. Finally, Asian Americans are a diverse group (Xia et al, 2013); whether the relationships found in our study of Chinese Americans can be replicated in other Asian American samples remains to be seen.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, our participants were from an area with a high percentage of Chinese Americans and a long history of Chinese immigration. As community characteristics – such as migration history, ethnic concentration, and neighborhood disadvantages – may influence the acculturation process (Kiang, Perreira, & Fuligni, 2011; Liu, Lau, Chen, Dinh, & Kim, 2009; White, Zeiders, Knight, Roosa, & Tein, 2014), future studies should test whether our results can be replicated in other Chinese American samples.…”
Section: Discussionmentioning
confidence: 94%